JOB INSECURITY, JOB SATISFACTION DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION PT. BIMA POLYPLAST DI SUKOHARJO - Ecky Gilang Ardi Saputra; Siti Maryam; Fithri Setya Marwati (JURNAL ILMIAH EDUNOMIKA, 2020)
The research aims to find out and describe the influence of simultaneously or partial job insecurity, job satisfaction and work environment towards turnover intention PT. Bima Polyplast Sukoharjo. This methodology research using quantitative descriptive research. The population was all employees PT. Bima Polyplast Sukoharjo is 72 people. The number of samples was determined with the formula Arikunto and the result 72 respondents. Sampling method using sensus sampling. The questionnaire used for data retrieval. Data analysis technique used was statistic analysis is multiple linier regression, F test, t test and determination coefficient. This test results the job insecurity, job satisfaction and work environment simultaneously and significance effect on turnover intention PT. Bima Polyplast Sukoharjo. Job insecurity influential positive and significance effect against the turnover intention PT. Bima Polyplast Sukoharjo. Job satisfaction influential negative and significance effect against the turnover intention PT. Bima Polyplast Sukoharjo. Work environment influential negative and significance to turnover intention PT. Bima Polyplast Sukoharjo. The results of the determination of the coefficient indicates job insecurity, job satisfaction and work environment have influence of 56,5% turnover intention PT. Bima Polyplast Sukoharjo. Suggestion in this research is companies are expected to pay more attention to noise levels at work that can interfere with work activities. This can be done by installing a silencer in the office. Keywords : Turnover Intention, Job Insecurity, Job Satisfaction, Work Environment